Effects of Impaired ATP Production and Glucose Sensitivity on Human β-cell Function: A Simulation Study - Félix - Martínez, G. J.; Azpiroz - Leehan, J.; Ávila - Pozos, R.; Godínez - Fernández, J. R. (Revista Mexicana de Ingenieria Biomedica, 2014)
In this paper we used a mathematical model to explore the effects of impaired ATP production and glucose sensitivity on the electrical response and insulin secretion of human β-cells. The model was extended by the addition of explicit empirical equations that describe recent experimental observations, namely, the increase of ATP as a function of glucose concentration and the oscillations in ATP at high glucose levels. Simulations were performed at selected glucose concentrations from an oral glucose tolerance test in normal subjects to evaluate the response of the human β-cell in normal and pathological scenarios. Our simulations reproduced experimental observations, such as the impaired insulin secretion as a consequence of β-cell dysfunction and restoration of electrical activity by the use of a sulfonylurea. Our results suggest that both reduced glucose sensitivity and impaired ATP production could be related to the pathogenesis of type 2 diabetes.